1975
DOI: 10.1111/j.1365-2133.1975.tb05116.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responses of patients with psoriasis and the effect of treatment with methotrexate

Abstract: A group of thirty-six patients of whom fourteen were being treated with methotrexate, were studied in order to assess T-lymphocyte function by in vitro techniques. Circulating T-lymphocytes in aliqots of blood were assessed by the rosetting technique. No differences were found in psoriatics, whether on methotrexate or not, compared with fifteen control subjects. Lymphocyte counts and lymphocyte transformation to phytohaemagglutinin (PHA) tended to be lower in the psoriatic group as a whole than in the controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Sensitization to DNCB was found to occur less frequently in patients with psoriasis as compared to non-psoriatics (Epstein & Maibach, 1965). Also, a lowered mitogenic response to PHA, Con A and PWM was observed (Levantine & Brostoff, 1976;Guilhou et al, 1975). recently noted decreased numbers of T cells in the peripheral blood of psoriatic patients as evaluated by Erosettes.…”
Section: Discussionmentioning
confidence: 98%
“…Sensitization to DNCB was found to occur less frequently in patients with psoriasis as compared to non-psoriatics (Epstein & Maibach, 1965). Also, a lowered mitogenic response to PHA, Con A and PWM was observed (Levantine & Brostoff, 1976;Guilhou et al, 1975). recently noted decreased numbers of T cells in the peripheral blood of psoriatic patients as evaluated by Erosettes.…”
Section: Discussionmentioning
confidence: 98%
“…These anomalies may be explained by a shift toward T suppressor cells of the T helper/T suppres sor cell ratio in the peripheral blood in psoriasis as reported 115]. There are, however, also reports suggesting a normal lymphocyte proliferation in patients with psoriasis [16][17][18]. Moreover, it has recently been found that soluble intcrlcukin-2 receptors, indicating lymphocyte activation, are elevated in psoriatic serum even after clinical remission 119-21 ].…”
Section: Discussionmentioning
confidence: 96%
“…A definite decrease in the E-rosette-forming lymphocytes has been reported by several investigators (Clot et al, 1975(Clot et al, , 1978Cormane, Hunyadi & Hamerlinck, 1977;Ghnski et al, 1978). Normal levels of E-rosette-forming cells have also been claimed (Levantine & Brostoff, 1975;Heid et al, 1976;Lischka, t976). The lymphocyte response to phytohaemagglutinin (PHA) in psoriatics has been reported to be normal (Hopsu-Havu & Helander, 1975;Clot et al, 1978) but that to concanavalin A (Con A) abnormally low (Clot et al, 1978).…”
mentioning
confidence: 88%